В школу: стихи : [для чтения родителями детям] / Агния Барто - Барто Агния Львовна (Малышам, 2002)
Экземпляры: ф.3 (2003) / Инвентарный номер: 45631 / Цена: / Сис.шифр: 84(2Рос-Рус)6-5 / Авт.знак: Б 26 / ГРНТИ: 17.82.93 / ББК: 84(2Рос-Рус)6-5